Low glycemic rice product - CGIAR Research Program on Rice (2021)
The effect of pre-cooking rice processing on human GI was investigated. Varieties were subjected to different processing, eaten and test subjects’ blood glucose levels monitored for 2 hours. Across varieties, rice that had been parboiled as paddy then polished had the lowest GI (< 27) and is best for diabetics.